2018
DOI: 10.1186/s13012-018-0792-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a knowledge mobilization model to prevent peripheral venous catheter-related adverse events: PREBACP study—a multicenter cluster-randomized trial protocol

Abstract: BackgroundPeripheral venous catheters are the most commonly used invasive devices in hospitals worldwide. Patients can experience multiple adverse events during the insertion, maintenance, and management of these devices. Health professionals aim to resolve the challenges of care variability in the use of peripheral venous catheter through adherence to clinical practice guidelines. The aim of this cluster-randomized controlled trial is to determine the efficacy of a multimodal intervention on incidence of adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…This study was essential to assess the clinical outcome indicators from CPG recommendations regarding the hospital environment as a baseline within a multimodal intervention [48]. We should integrate the best evidence while deepening the motivations and beliefs of health professionals during decision-making for successful implementation, but we must also pay attention to the context, the great neglected in the field of implementation science [49].…”
Section: Discussionmentioning
confidence: 99%
“…This study was essential to assess the clinical outcome indicators from CPG recommendations regarding the hospital environment as a baseline within a multimodal intervention [48]. We should integrate the best evidence while deepening the motivations and beliefs of health professionals during decision-making for successful implementation, but we must also pay attention to the context, the great neglected in the field of implementation science [49].…”
Section: Discussionmentioning
confidence: 99%
“…The table is sorted on type of article, type of use of the PARIHS framework, author and year of publication Authors Ref Year of publ. Full title Country(ies) Setting PARIHS used: Type of article To plan/deliver an intervention In the analysis a In the evaluation of findings In any other way Chinman, Daniels, et al [ 23 ] 2017 Provision of peer specialist services in VA patient aligned care teams: Protocol for testing a cluster randomized implementation trial USA Primary health care setting Protocol Gordon, Lee, et al [ 24 ] 2018 A complex culturally targeted intervention to reduce Hispanic disparities in living kidney donor transplantation: An effectiveness-implementation hybrid study protocol USA Community/Social care setting Protocol Roberge, Fournier, et al [ 25 ] 2013 Implementing a knowledge application program for anxiety and depression in community-based primary mental health care: A multiple case study research protocol Canada Primary health care setting Protocol Blanco-Mavillard, Bennasar-Veny, et al [ 26 ] 2018 Implementation of a knowledge mobilization model to prevent peripheral venous catheter-related adverse events: PREBACP study-a multicenter cluster-randomized trial protocol Spain Hospital setting Protocol Bucknall, Harvey, et al [ 27 ] 2017 Prioritizing Responses Of Nurses To deteriorating patient Observations (PRONTO) protocol: Testing the effectiveness of a facilitation intervention in a pragmatic, cluster-randomized trial with an embedded process evaluation and cost analysis Australia Hospital setting …”
Section: Resultsmentioning
confidence: 99%
“…In these articles, the analysis was performed in different ways, primarily through mapping and comparing PARIHS to other frameworks or models or even policies, but also for general discussions on implementation and evidence-based practice. Among the 185 articles that reported using the PARIHS framework in the analysis, there were also 22 protocols where authors reported that the intention was to use the framework in the analysis [23][24][25][26][27][28][29][30][31][32][33][34][35][47][48][49][50][51][52][53][54][55].…”
Section: The Application Of Parihs In Data Analysismentioning
confidence: 99%
“…The quality of healthcare can be significantly improved by designing interventions to improve the efficacy of the first puncture, selecting the most appropriate catheter and reducing the pain of peripheral cannulation, thus minimising its adverse effects [10,15,33]. Early referral to a vascular access specialist team (VAST) with advanced knowledge and skills in catheter insertion and care, or interventions putting into practice the recommendations of experts in the management of vascular catheters, can help to avoid the adverse events associated with cannulation, and their associated costs [13,34].…”
Section: Discussionmentioning
confidence: 99%